The paradox of investment: A contribution to the theory of demand-led economic growth - Leão, E. R.; Leão, P. R. (Review of Political Economy, 2024)
This paper has two purposes. The first is to argue that aggregate investment may be subject to the following paradox. A rise in investment decided by firms to correct overutilization of their production capacity may generate less capacity than demand — and hence cause a paradoxical rise in overutilization. This will in turn lead to even more investment, and so on — the result being the self-sustained rises in output that characterize economic expansions. The second purpose of the paper is to put forward one reason why the above paradox of investment will lose strength as expansions progress, and may eventually disappear leading to their end. That reason may be summarized as follows. As net investment increases along expansions, the effect of investment on production capacity rises relative to its effect on demand — and, as a result, the rise in utilization slows down. Moreover, as net investment eventually grows to a high level, the effect of investment on capacity may become bigger than its effect on demand. If this happens, utilization will stop rising and start falling, and thus the same may happen with investment and output.